2013
DOI: 10.1055/s-0033-1344958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ki-67 index in EUS–FNA specimens for the assessment of malignancy risk in pancreatic neuroendocrine tumors

Abstract: Grading of PNETs by the highest Ki-67 index in EUS-FNA specimens with adequate cellularity has a high concordance with grading of resected specimens, and can predict long term patient survival with high accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
153
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(168 citation statements)
references
References 27 publications
9
153
1
1
Order By: Relevance
“…Similar observations were made by Hasegawa et al, who showed that majority of volume of G2 tumours was in fact composed of G1 areas [12].…”
Section: Ki67 LI Heterogeneity In the Context Of Cssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar observations were made by Hasegawa et al, who showed that majority of volume of G2 tumours was in fact composed of G1 areas [12].…”
Section: Ki67 LI Heterogeneity In the Context Of Cssupporting
confidence: 89%
“…As mentioned above, Hasegawa et al documented that NET G2 consist in majority from G1 areas [12]. Goodell et al distinguished 3 groups of pancreatic NET based on Ki67 LI in a single-field HS and 10 consecutive fields average: 13/45 (28.9%) and 6/45 (13.3%) were scored as G1 and G2 based on both scoring techniques (respectively), but as many as 26/45 (57.8%) were scored as G2 based on a single HS, but as G1 based on 10 consecutive fields average [24].…”
Section: Ki67 LI Heterogeneity Beyond Single Hs or Csmentioning
confidence: 87%
See 3 more Smart Citations